Bear and Bird : the stick and other stories - Jarvis, 1985- (Jarvis, 1985- Bear and Bird., 2025)
"Bear and Bird are the kind of friends who just want to make each other happy. So when Bird realizes Bear has had a leaf stuck to his face all day, she goes to comical extremes not to embarrass him--even if it means encouraging a new trend. And when they both grab the same excellent stick on a windy day, they outdo each other trying to give it back--until Bear comes up with a better use for their imagination"--